Vertebral haemangiomatosis – two clinical case reports - Caridade, Sofia (2008)
Haemangiomas are benign lesions arising from proliferation of blood vessels and represent about 1% of all bone tumours. They are usually asymptomatic. Nevertheless, they may present as a vague discomfort progressing to constant pain. Neurological complications can be found if epidural extension of the tumour exists.We report two cases of vertebral haemangiomatosis in which a lesion assumes an aggressive behaviour, very uncommon in these cases. Hemangiomas were present in other vertebral bodies, with typical behaviour and imagiological characteristics.